Preservice Teachers’ Self-Efficacy Beliefs for Promoting Learner Autonomy in English Language Education - Borja Manzano Vázquez; Flávia Vieira; Manuel Jiménez Raya (Profile: Issues in Teachers' Professional Development)
Preservice teachers’ self-efficacy beliefs influence their willingness and ability to promote learner autonomy in schools. This study aimed to investigate the self-efficacy beliefs of a group of preservice teachers in an initial English language teacher education programme, where they were prepared and encouraged to promote pedagogy for autonomy. Data were gathered through questionnaires and focus group interviews. Findings indicate a relatively high sense of self-efficacy regarding the promotion of learner autonomy. Personal and contextual factors that enable or constrain those beliefs were identified, with implications for how initial teacher education programmes may foster preservice teachers’ readiness to value and enact learner-centred pedagogies.